Genetic structure analysis of several peroral infectivity factor gene in Spodoptera litura Nucleopolyhedrovirus - Christian, Michael; Kusumah, Yayi Munara; Mutaqin, Kikin Hamzah (Universitas Lampung, 2025)
Spodoptera litura Nucleopolyhedrovirus (SpltNPV) is an entomopathogenic virus from the Baculoviridae family, currently under development as a biological control agent for cutworm Spodoptera litura. The NPV’s ability to infect its pest host can be determined by expression of pif protein complex by pif gene. The research aims to acquire genetic character information of the pif gene of SpltNPV from Bogor. Amplification of the NPV gene was carried out using the specific primers to amplifies two types of pif gene. The PCR products were sequenced then the DNA sequences were analyzed with the BioEdit and BLAST programs. The PCR amplification results showed that the size of the sample DNA fragment was 900 bp, 1300 bp and 710 bp. Based on the sequence analysis results, SpltNPV isolates from Bogor are closely related to SpltNPV and SpliNPV isolates from China. The highest nucleotide homology values of Pif-1, Pif-2, and Pif-3 gene were 99.56%, 99.37% and 100%, respectively. Based on the results of phylogenetic analysis, HearNPV isolates from Bogor belong to the same group as the NPVs that infect the species Spodoptera litura and closely related to NPV that infect Spodoptera littoralis. The amino acid sequence analysis showed the number of mutated sites in pif-1, pif-2, and pif-3 in this study are 1, 3, and 0, respectively, which indicates that protein mutation in SpltNPV Bogor did not significantly alter the viral infection process.